Diltiazem-Associated Cardiogenic Shock in Thyrotoxic Crisis. (November 2018) - Subahi, Ahmed; Ibrahim, Walid; Abugroun, Ashraf
Abstract : Clinical Features: The patient we present is a 39-year-old woman with a history of hyperthyroidism who developed fast atrial fibrillation secondary to thyrotoxic storm. After the initiation of intravenous diltiazem drip, she developed hypotension, bradycardia, then asystole cardiac arrest. Therapeutic Challenge: It is well known that calcium channel blockers and beta blockers should be used with extreme caution if the patient with thyroid storm has decompensated heart failure with reduced ejection fraction. Despite this, it is recognized that guidelines for the management of thyroid storm do not include an algorithm of action in this situation. Thus, dealing with low-output failure during thyroid storm may pose a critical challenge. Solution: A significant portion of patients with thyrotoxic storm have an underlying low-output cardiac failure. Early identification, proper hemodynamic monitoring, and administration of the agents with appropriate pharmacodynamic profile and therapeutic potentials are essential to avoid treatment-induced cardiogenic shock.